Perchloric Acid-Functionalized Silica Nanosphere as Novel and Green Catalyst for the Synthesis of 2H-indazolo[2,1-b]phthalazinetrione Derivatives - Chegeni, Mahdieh; Khazaei, Ardeshir; Rahmati, Sadegh; Hossein Fekri, Mohammad (Letters in Organic Chemistry, 2015)
In this report, synthesis and characterization of silica perchloric acid nanosphere as a novel and heterogeneous catalyst are described. It has a spherical shape and the particle size is between 75 and 100 nm. The catalytic activity has been investigated in coupling reaction involving a variety of aldehydes, phthalhydrazide, dimedone at 80°C under solvent-free conditions. This method offers advantages such as good yields, simple conditions, shorter reaction time, and reusable activity catalyst.
Keywords: dimedone